Lanthanide(III) Based Complexes Containing 5, 7‐Dimethyl‐1, 2, 4‐triazolo[1, 5‐a]pyrimidine as Long‐Lived Photoluminescent Antiparasitic Agents. Issue 3 (15th January 2020) - Esteban‐Parra, Ginés M.; Moscoso, Inmaculada; Cepeda, Javier; García, Jose A.; Sánchez‐Moreno, Manuel; Rodríguez‐Diéguez, Antonio; Quirós, Miguel
Abstract : We report the synthesis and characterization of a new family of lanthanide‐based compounds containing a triazolopyrimidine derivative ligand, having the [Ln(H2 O)9 ][Ln(NO3 )6 ]· 9dmtp Ln = La (1 ) and Nd (2 ) and [Ln(H2 O)3 (NO3 )3 ]· 3dmtp Ln = Eu (3 ), Gd (4 ), Tb (5 ), Dy (6 ), Er (7 ) and Yb (8 ), where dmtp = dimethyl‐1, 2, 4‐triazolo[1, 5‐ a ]pyrimidine formulae. These materials possess variable structures and show variable luminescence properties, as well as interesting antiparasitic activities against pathogenic agent of Leishmaniasis and Chagas disease, which makes these compounds excellent candidates to be further investigated to develop new drugs against those neglected diseases. Moreover, the measurement of the photoluminescence properties of Eu‐ and Tb‐counterparts revealed that the dmtp ligand possesses accessible triplet states which can not only promote an efficient antenna effect that enhances lanthanide‐based emissions but also prolong them to several milliseconds. Abstract : The synthesized compounds possess long‐lived luminescence emission, as well as interesting antiparasitic activities against the pathogenic agent of Leishmaniasis and Chagas disease, which makes these compounds excellent candidates to be further investigated to develop new drugs against those neglected diseases.